The Impact of Culture Shock and Psychological Adjustment on Mental Well-Being in International Students - Ayub, Maria; Mehmood, Haziq; Nazir, Arooj (Pakistan Journal of Humanities and Social Sciences, 2024)
Cultural shock is attributed as a psychological response experienced due to adjusting into a new cultural environment. This present study research explored the impact of cultural shock on psychological adjustment and mental well-being. It was hypothesized that there will be an inverse relationship of Culture shock and Mental Well-Being in international students. For this purpose, correlational cross-sectional research design was used. The sample included 192 international students with the age range of 18 to 40 (M=21.02, SD=1.50) including 154 men and 38 women recruited through using convenience sampling strategy. A self-constructed demographic sheet, psychological adjustment scale (Ryff & Keyes,1995)., Warwick-Edinburgh mental wellbeing scale (Tennant et al., 2007) and culture shock scale (Mumford, 1998) were used for the assessment. The result of Pearson product moment correlation illustrated the inverse relationship between culture shock and psychological adjustment in students. This revealed that examining the links between the evaluation elements could improve the rational understanding of psychological outcomes of acculturation related to personal variability factors. Such insights could also guide host university communities in bolstering the self-esteem and self-belief of their international student peers, aiding them in navigating their psychological adaptation challenges.